Children's pictures of COVID-19 and measures to mitigate its spread: An international qualitative study. (November 2021) - Bray, Lucy; Blake, Lucy; Protheroe, Jo; Nafria, Begonya; de Avila, Marla Andreia Garcia; Ångström-Brännström, Charlotte; Forsner, Maria; Campbell, Steve; Ford, Karen; Rullander, Anna-Clara; Robichaud, Fanny; Nolbris, Margaretha Jenholt; et al.
Objectives: To gain insight into children's health-related knowledge and understanding of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV2) and COVID-19, and measures adopted to mitigate transmission. Design: A child-centred qualitative creative element embedded in an online mixed-methods survey of children aged 7–12 years. Setting: Children participated in the study in six countries – the UK, Australia, Sweden, Brazil, Spain and Canada. Method: A qualitative creative component, embedded in an online survey, prompted children to draw and label a picture. Children were recruited via their parents using the researchers' professional social media accounts, through known contacts, media and websites from health organisations within each country. Analysis of the form and content of the children's pictures took place. Results: A total of 128 children (mean age 9.2 years) submitted either a hand-drawn ( n = 111) or digitally created ( n = 17) picture. Four main themes were identified which related to children's health-related knowledge of (1) COVID-19 and how it is transmitted; (2) measures and actions to mitigate transmission; (3) places of safety during the pandemic; and (4) children's role in mitigating COVID-19 transmission. Conclusion: Children's pictures indicated a good understanding of the virus, how it spreads and how to mitigate transmission. Children depicted their actions during the pandemic as protecting themselves, their families and wider society.